Neisseria meningitidis activates pyroptotic pathways in a mouse model of meningitis: role of a two-partner secretion system - Chiara Pagliuca; Roberta Colicchio; Silvia Caterina Resta; Adelfia Talà; Elena Scaglione; Giuseppe Mantova; Leonardo Continisio; Leonardo Continisio; Caterina Pagliarulo; Cecilia Bucci; Pietro Alifano; Paola Salvatore; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
There is evidence that in infected cells in vitro the meningococcal HrpA/HrpB two-partner secretion system (TPS) mediates the exit of bacteria from the internalization vacuole and the docking of bacteria to the dynein motor resulting in the induction of pyroptosis. In this study we set out to study the role of the HrpA/HrpB TPS in establishing meningitis and activating pyroptotic pathways in an animal model of meningitis using a reference serogroup C meningococcal strain, 93/4286, and an isogenic hrpB knockout mutant, 93/4286ΩhrpB. Survival experiments confirmed the role of HrpA/HrpB TPS in the invasive meningococcal disease. In fact, the ability of the hrpB mutant to replicate in brain and spread systemically was impaired in mice infected with hrpB mutant. Furthermore, western blot analysis of brain samples during the infection demonstrated that: i. N. meningitidis activated canonical and non-canonical inflammasome pyroptosis pathways in the mouse brain; ii. the activation of caspase-11, caspase-1, and gasdermin-D was markedly reduced in the hrpB mutant; iii. the increase in the amount of IL-1β and IL-18, which are an important end point of pyroptosis, occurs in the brains of mice infected with the wild-type strain 93/4286 and is strongly reduced in those infected with 93/4286ΩhrpB. In particular, the activation of caspase 11, which is triggered by cytosolic lipopolysaccharide, indicates that during meningococcal infection pyroptosis is induced by intracellular infection after the exit of the bacteria from the internalizing vacuole, a process that is hindered in the hrpB mutant. Overall, these results confirm, in an animal model, that the HrpA/HrpB TPS plays a role in the induction of pyroptosis and suggest a pivotal involvement of pyroptosis in invasive meningococcal disease, paving the way for the use of pyroptosis inhibitors in the adjuvant therapy of the disease.